2020
DOI: 10.20950/1678-2305.2020.46.2.573
|View full text |Cite
|
Sign up to set email alerts
|

Nile Tilapia Nursery in a Biofloc System: Evaluation of Different Stocking Densities

Abstract: This trial aimed to evaluate the growth performance and hematological parameters of Nile tilapia (Oreochromis niloticus) GIFT strain during nursery using different stock densities in a biofloc system. The experiment was conducted in circular tanks (400 L) with sexually reversed fish, weighing 6.74 ± 0.37 g, over a period of 35 days. Five treatments with three replicates each were used in a completely randomized design. The treatments were as follows: T1 (200 fishes m-3); T2 (300 fishes m-3); T3 (400 fishes m-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 50 publications
4
8
0
Order By: Relevance
“…Silva et al ( 2020) also observed higher values of SS and TSS with higher feeding rates, having reportedmaximum values of 225 mL L -1 and 1,450 mg L -1 of solids throughout the rearing of tilapia juveniles when fed with 100% of the satiety. Tilapia nursery studies in a biofloc system demonstrated a wide variation in the values of SS (0.5 to 65 mL L -1 ) and TSS (200 to 1,600 mg L -1 ) (Martins et al, 2017, Lima et al, 2018, Martins et al, 2019, Correa et al, 2020, Durigon et al, 2020, Hisano et al, 2020, Vicente et al, 2020. In this study, the solids were managed to maintain mean values close to 30 mL L -1 and 600 mg L -1 .…”
Section: Resultsmentioning
confidence: 71%
“…Silva et al ( 2020) also observed higher values of SS and TSS with higher feeding rates, having reportedmaximum values of 225 mL L -1 and 1,450 mg L -1 of solids throughout the rearing of tilapia juveniles when fed with 100% of the satiety. Tilapia nursery studies in a biofloc system demonstrated a wide variation in the values of SS (0.5 to 65 mL L -1 ) and TSS (200 to 1,600 mg L -1 ) (Martins et al, 2017, Lima et al, 2018, Martins et al, 2019, Correa et al, 2020, Durigon et al, 2020, Hisano et al, 2020, Vicente et al, 2020. In this study, the solids were managed to maintain mean values close to 30 mL L -1 and 600 mg L -1 .…”
Section: Resultsmentioning
confidence: 71%
“…The increased oxygen‐carrying capacity of blood might be the response of fish against crowding chronic stress and high energy demand situations (Montero et al, 2001). In contrast, a higher level of haemoglobin was reported in Nile tilapia ( Oreochromis niloticus ) cultivated in biofloc system at 400 fish m −3 than 600 fish m −3 density; however, higher value of haemoglobin was not significantly differed with other lower density treatments, that is 200, 300 and 500 fish m −3 (Vicente et al, 2020).…”
Section: Discussionmentioning
confidence: 92%
“…While experimenting with different stocking densities of the Nile tilapia and BFT, Haridas et al (2017) and Vicente et al (2020) also observed an increase in the amount of ammonia with increasing fish density. However, these studies did not report any significant relationship between the concentration of nitrite and nitrate in the water with stocking density, probably due to the use of organic carbon in their studies to regulate nitrogen in the bioflocs.…”
Section: Water and Solid Analysesmentioning
confidence: 89%
“…However, as per the heterotrophic route, one gram of ammonia generates 8.07 g of microbial biomass, indicating a much higher amount of solid generation, compared to the nitrification process (0.20 g) (Ebeling et al, 2006). Incidentally, Vicente et al (2020) also reported an excess amount of total solids (> 1000 mg L -1 ) at all stock densities (200 to 600 fish m -3 with weight ranging between 20 to 30 g per fish) evaluated in tilapia. This might be due to the use of sugar to neutralize the high concentration of ammonia present in a system even before the fish reached maturity.…”
Section: Water and Solid Analysesmentioning
confidence: 92%
See 1 more Smart Citation